2017
DOI: 10.1589/jpts.29.707
|View full text |Cite
|
Sign up to set email alerts
|

The effect of bridge exercise method on the strength of rectus abdominis muscle and the muscle activity of paraspinal muscles while doing treadmill walking with high heels

Abstract: [Purpose] The purpose of this research is to investigate the effect of the method of bridge exercise on the change of rectus abdominis muscle and the muscle activity of paraspinal muscles while doing treadmill walking with high heels. [Subjects and Methods] The subjects of this research are healthy female students consisting of 10 persons performing bridge exercises in a supine group, 10 persons performing bridge exercises in a prone group, and 10 persons in a control group while in S university in Busan. Brid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The results showed that deep abdominal muscles (internal oblique) were more activated than RA, and differences in subjects who practiced Pilates activated core muscles and had better stability than those who had not practiced Pilates before (Lee 2021). Most of the studies exploring the effect of Pilates on abdominal muscles have a focus on deeper muscles (Gibbons & Bird 2019, Kim et al 2011, Escamilla et al 2015, Moon et al 2015, Kang et al 2017, Cho & Jeon 2013 or RA and EO in association with trunk muscles (Park et al 2015, Calatayud et al 2019, Lee et al 2016, Tahan et al 2016, or the use of other tools to assess, such as ultrasound to measure muscle thickness (Gibbons & Bird 2019, Moon et al 2015, Cho & Jeon 2013, Tahan et al 2016 or other unstable surfaces (Escamilla et al 2015, Feldwieser et al 2012, Lee et al 2016. Pereira et al (2017) reported that RA and EO were more activated during the single-leg stretch exercise compared to other Pilates positions, and this change in activation occurred within the first session of Pilates (Pereira et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that deep abdominal muscles (internal oblique) were more activated than RA, and differences in subjects who practiced Pilates activated core muscles and had better stability than those who had not practiced Pilates before (Lee 2021). Most of the studies exploring the effect of Pilates on abdominal muscles have a focus on deeper muscles (Gibbons & Bird 2019, Kim et al 2011, Escamilla et al 2015, Moon et al 2015, Kang et al 2017, Cho & Jeon 2013 or RA and EO in association with trunk muscles (Park et al 2015, Calatayud et al 2019, Lee et al 2016, Tahan et al 2016, or the use of other tools to assess, such as ultrasound to measure muscle thickness (Gibbons & Bird 2019, Moon et al 2015, Cho & Jeon 2013, Tahan et al 2016 or other unstable surfaces (Escamilla et al 2015, Feldwieser et al 2012, Lee et al 2016. Pereira et al (2017) reported that RA and EO were more activated during the single-leg stretch exercise compared to other Pilates positions, and this change in activation occurred within the first session of Pilates (Pereira et al 2017).…”
Section: Discussionmentioning
confidence: 99%